Fracture Analysis of Brittle Materials Based on Nonlinear FEM and Application in Arch Dam with Fractures. (28th October 2013) - Pan, Yuanwei; Liu, Yaoru; Cui, Zhixiong; Chen, Xin; Yang, Qiang
Abstract : Current fracture analysis models based on fracture mechanics or continuum damage mechanics are still limited in the application to three-dimensional structure. Based on deformation reinforcement theory coming from elastoperfect plastic theory, unbalanced force is proposed to predict initiation and propagation of cracks. Unbalanced force is the driving force of time-dependent deformation according to Perzyna's viscoplasticity theory. It is also related to the damage driving force in viscoplastic damage model. The distribution of unbalanced force indicates cracks initiation area, while its direction predicts possible cracks propagation path. Uniaxial compression test of precrack specimen is performed as verification to this method. The trend and distribution of cracks are in good agreement with numerical results, proving that unbalanced force is feasible and effective for fracture analysis. The method is applied in fracture analysis of Xiaowan high arch dam, which is subjected to some cracks in dam due to the temperature control program. The results show that the deformation and stress of cracks and the stress characteristics of dam are insensitive to grouting of cracks. The existing cracks are stable and dam heel is still the most possible cracking position.